Optimizing the Role of Indonesian Navy Diplomacy in Supporting the Policy Pillars of Maritime Diplomacy - Prastyawan, Herry (International Journal of Social and Management Studies, 2023)
The policy of maritime diplomacy is a strategic foundation for countries that have large territorial waters and significant maritime potential. In the context of Indonesia, as the largest archipelagic country in the world, maritime diplomacy is crucial to maintaining sovereignty, security and national interests in its maritime area. In an effort to support the pillars of maritime diplomacy policy, the Indonesian Navy has a strategic and central role. This research is based on literature studies and data analysis relevant to maritime issues and the role of the Indonesian Navy in diplomacy. Factors that drive the important role of the Indonesian Navy in maritime diplomacy will be highlighted, including the challenges faced. It is hoped that an in-depth understanding of how the Indonesian Navy can play an optimal role in supporting the pillars of Indonesia's maritime diplomacy policy is expected to be obtained. Efforts to build regional and international cooperation, protect maritime economic interests, maintain maritime security, and overcome existing challenges, are the basis for dealing with the complexity of dynamics in increasingly complex maritime areas. That way, maritime diplomacy can be an effective instrument in achieving national goals and bringing benefits to the security and welfare of the nation.